Synergistic effect in simultaneous removal of cationic and anionic heavy metals by nitrogen heteroatom doped hydrochar from aqueous solutions - Hee-Gon Kim; Lee, Seon Yong; Choi, Jae Woo; Jung, Kyung Won (Pergamon Press Ltd., 2023)
Industrial wastewater typically contains both cationic and anionic heavy metals; therefore, their simultaneous removal must be considered to ensure environmental sustainability. Herein, nitrogen heteroatom (N) doped hydrochar derived from corncob was prepared via facile NH4Cl-aided hydrothermal carbonization and used for the simultaneous adsorption of divalent copper (Cu(II)) and hexavalent chromium (Cr(VI)) in aqueous solutions. During hydrothermal carbonization, NH4Cl played a vital role as the porogen and N dopant, which contributed to the efficient adsorption affinity toward coexisting Cu(II) and Cr(VI). The theoretical maximum adsorption capacities of the N-doped hydrochar were determined to be 1.223 mmol/g for Cu(II) and 1.995 mmol/g for Cr(VI), which were much better than those of the pristine hydrochar. Furthermore, in the binary-component system, the synergistic effect between Cu(II) and Cr(VI) significantly promoted the adsorption affinity of N-doped hydrochar, resulting in adsorption capacities for Cu(II) and Cr(VI) 9.48 and 1.92 times higher than those of the single-component system, respectively. A series of adsorption experiments and spectroscopic analyses demonstrated that multiple mechanisms, including electrostatic shielding, cation bridging, and redox reactions, mutually contributed to the synergistic effect in the adsorption of coexisting Cu(II) and Cr(VI). Overall, the N-doped hydrochar proved to be effective in simultaneously removing both cationic and anionic heavy metal pollutants.